2014
DOI: 10.1371/journal.pone.0094882
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Variants in Obesity

Abstract: Heritability estimates for body mass index (BMI) variation are high. For mothers and their offspring higher BMI correlations have been described than for fathers. Variation(s) in the exclusively maternally inherited mitochondrial DNA (mtDNA) might contribute to this parental effect. Thirty-two to 40 mtDNA single nucleotide polymorphisms (SNPs) were available from genome-wide association study SNP arrays (Affymetrix 6.0). For discovery, we analyzed association in a case-control (CC) sample of 1,158 extremely ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
1
27
4
Order By: Relevance
“…mtDNA T4216C) and were formerly described as sister haplogroups with a common root [ 30 ]. Our results contradict those of Knoll et al [ 8 ], who found no association of mtDNA haplogroups and obesity. However, it should be noted that the cases and control subjects of the Knoll study were either of French or German ancestry [ 31 ]; therefore, differences of geographic origin might account for the different results of the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…mtDNA T4216C) and were formerly described as sister haplogroups with a common root [ 30 ]. Our results contradict those of Knoll et al [ 8 ], who found no association of mtDNA haplogroups and obesity. However, it should be noted that the cases and control subjects of the Knoll study were either of French or German ancestry [ 31 ]; therefore, differences of geographic origin might account for the different results of the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Knoll et al reported a higher frequency of the polymorphism T16189C among extremely obese cases (17% vs. 9%) [ 8 ]. This variant would give rise to an uninterrupted poly-C tract from np 16184 to 16193 and possibly lead to heteroplasmic length variation of different mtDNA molecules within the same person [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower expression levels of these two genes correlates with insulin resistance [ 60 ]. Furthermore, an association with obesity was found for a frequent allele of the human ATP6 gene [ 61 , 62 ]. Similar to mt : Col and mt : Cyt-b , the Drosophila homolog of ATP6 , mt : ATPase6 , is also upregulated when Ets96B is knocked down in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have shown that the mitochondrial OXPHOS system is important for regulation of adipogenesis in hASCs and that its inhibition at the level of mtDNA replication (NRTIs), organelle protein synthesis (antibiotics) or function (TBTC) can either inhibit or promote adipogenesis in vitro . Because important OXPHOS components are mtDNA-encoded and OXPHOS capacity is affected by mtDNA haplogroup ( Gomez-Duran et al, 2010 , 2012 ), genetic variability in mtDNA could affect adipocyte differentiation and related phenotypes such as obesity ( Knoll et al, 2014 ; Nardelli et al, 2013 ; Yang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%